FET-PET for malignant glioma treatment planning - Niyazi, Maximilian; Geisler, Julia; Siefert, Axel; Schwarz, Silke Birgit; Ganswindt, Ute; Garny, Sylvia; Schnell, Oliver; Suchorska, Bogdana; Kreth, Friedrich Wilhelm; Tonn, Jörg Christian; Bartenstein, Peter; Fougre, Christian La; et al. (Radiotherapy and Oncology, 2011)
Background and purpose: The aim of this study was to compare MRI-based morphological gross tumour volumes (GTVs) to biological tumour volumes (BTVs), defined by the pathological radiotracer uptake in positron emission tomography (PET) imaging with 18F-fluoroethyltyrosine (FET), subsequently clinical target volumes (CTVs) and finally planning target volumes (PTVs) for radiotherapy planning of glioblastoma. Patients and methods: Seventeen patients with glioblastoma were included into a retrospective protocol. Treatment-planning was performed using clinical target volume (CTV = BTV + 20 mm or CTV = GTV + 20 mm + inclusion of the edema) and planning target volume (PTV = CTV + 5 mm). Image fusion and target volume delineation were performed with OTP-Masterplan®. Initial gross tumour volume (GTV) definition was based on MRI data only or FET-PET data only (BTV), secondarily both data sets were used to define a common CTV. Results: FET based BTVs (median 43.9 cm3) were larger than corresponding GTVs (median 34.1 cm3, p = 0.028), in 11 of 17 cases there were major differences between GTV/BTV. To evaluate the conformity of both planning methods, the index (CTVMRT ∩ CTV FET)/(CTVMRT ∪ CTVFET) was quantified which was significantly different from 1 (0.73 ± 0.03, p < 0.001). Conclusion: With FET-PET-CT planning, the size and geometrical location of GTVs/BTVs differed in a majority of patients. It remains open whether FET-PET-based target definition has a relevant clinical impact for treatment planning. © 2011 Elsevier Ireland Ltd All rights reserved. Radiotherapy and Oncology.
CRIS-Team Scopus Importer:2023-09-13
Keywords: BTV; FET-PET; Malignant glioma; Planning study; Target delineation